2013
DOI: 10.1080/00405000.2013.827390
|View full text |Cite
|
Sign up to set email alerts
|

Annealing effects on structural changes and thermal shrinkage of poly(lactic acid) draw-textured filaments

Abstract: To control the thermal shrinkage of poly(lactic acid) draw-textured yarns, the annealing effects on structural changes and thermal shrinkage were investigated. Specifically, annealing temperatures of 100 and 160°C and annealing times of 10-50 min per every 10 min were investigated. Differential scanning calorimetry thermograms revealed that filaments annealed at 100°C produced double melting peaks due to crystal imperfections, while those annealed at 160°C for more than 30 min showed a single melting peak. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…19,20 To fabricate the braided stent, stent is first braided on a special mold, and then annealed at 100 C for 1 h. 21 Many studies have shown that shrinkage occurs during unconstrained annealing process for solid-state drawn PLLA monofilaments. 22,23 However, the PLLA monofilaments used for weaving cannot shrink freely since they are taut with constrained ends in the braided stents.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 To fabricate the braided stent, stent is first braided on a special mold, and then annealed at 100 C for 1 h. 21 Many studies have shown that shrinkage occurs during unconstrained annealing process for solid-state drawn PLLA monofilaments. 22,23 However, the PLLA monofilaments used for weaving cannot shrink freely since they are taut with constrained ends in the braided stents.…”
Section: Introductionmentioning
confidence: 99%
“…In this study the Young's Modulus and tensile strength increased by 30% and 20% respectively following annealing due to a higher degree of crystallinity. The decrease in Young's Modulus at 90 o C and UTS could have occurred due to molecular deterioration or delamination of adjacent layers caused by thermal annealing (Seo et al, 2014). However, there was no evidence of thermal degradation within this study.…”
Section: Mechanical Propertiesmentioning
confidence: 58%
“…Furthermore, yarn shrinkage is increased when PLA yarns are textured, which further impairs downstream processes. Colour fastness also seems lower than in standard yarns, especially for bright colours [100][101][102]. Other research successfully created socks out of textured PLA yarns [103], and PLA yarn dyed with bio-based turmeric (or curcuma) could even be processed into socks [104].…”
Section: Biopolymers In False-twist Texturingmentioning
confidence: 99%